Public Spending: The Effect of Political Fragmentation - Zirgulis, Aras; Eitutis, Mantas (Socialiniai tyrimai, 2016)
This paper analyses the effects of political fragmentation of central government expenditure. We have defined political fragmentation as the number of spending ministers in the government and the number of political parties in the governing coalition. Previous studies have found evidence of a positive relationship between the two sides. We have tested this relationship using more recent data (from 1999-2011) on a panel of 29 countries. Furthermore, due to an intense debate about the effects of monetary policy on fiscal discipline, we also investigate a rather unorthodox idea that the absence of independent monetary policy in a country diminishes the effects of political fragmentation. We have found that the coalition size interacting with economic growth has an effect on public spending but that the traditional measures of political fragmentation, in themselves, do not have any effect - in contradiction with past findings. We have also failed to find a relationship between independent monetary policy on fiscal discipline.
Keywords: government expenditure; political fragmentation; political economy; monetary policy